Fetal Alcohol Syndrome Disorder: diminished responsibility and mitigation of sentence. (February 2018) - Scott, Russ
Objective: The objective of this study was to consider the implications of a recent Western Australia Court of Appeal decision in which an indigenous youth who had been sentenced for the manslaughter of his neonate child was later diagnosed with Fetal Alcohol Syndrome Disorder. Conclusion: The increased use of the 2016 Australian guide to the diagnosis of fetal alcohol spectrum disorder should be encouraged to enable clinicians to not only diagnose and manage Fetal Alcohol Syndrome Disorder, but also counsel families to prevent it.